2014
DOI: 10.1111/papr.12171
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin Does Not Affect Sperm Production in Healthy Volunteers: A Randomized, Double‐blind, Placebo‐controlled, Noninferiority Study

Abstract: One hundred and nine subjects received placebo and 111 subjects received pregabalin. The difference between placebo and pregabalin with respect to the percentage of subjects with a ≥ 50% reduction from baseline in sperm concentration at End of Study was 6% (95% CI: -2.29 to 14.3%). Noninferiority of pregabalin compared to placebo was declared as the upper bound of the 95% CI was less than the prespecified noninferiority margin of 20%. There were no significant differences between placebo and pregabalin groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…With regard to differences in the conclusions of the studies, the peer-reviewed reports for seven drugs were found to contradict the information present in the DailyMed labels. Four of the drugs had contradictory findings in human studies (pregabalin, colchicine, cortisone, and dexamethasone [ 14 , 24 , 25 , 27 , 28 ]), and one drug had contradictory findings in a study performed in rats (gabapentin [ 15 ]). The pro-drug for another agent (AZA, which is metabolized to 6-mercaptopurine) was reported to have no effects in humans or animals [ 36 , 37 ], and there was conflicting data in the literature regarding the effects of methotrexate in humans [ 40 , 41 ].…”
Section: Agreement Of the Peer-reviewed Literature With The Informatimentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to differences in the conclusions of the studies, the peer-reviewed reports for seven drugs were found to contradict the information present in the DailyMed labels. Four of the drugs had contradictory findings in human studies (pregabalin, colchicine, cortisone, and dexamethasone [ 14 , 24 , 25 , 27 , 28 ]), and one drug had contradictory findings in a study performed in rats (gabapentin [ 15 ]). The pro-drug for another agent (AZA, which is metabolized to 6-mercaptopurine) was reported to have no effects in humans or animals [ 36 , 37 ], and there was conflicting data in the literature regarding the effects of methotrexate in humans [ 40 , 41 ].…”
Section: Agreement Of the Peer-reviewed Literature With The Informatimentioning
confidence: 99%
“…Moreover, some of the findings included in the drug labels are difficult to interpret. For example, although the current drug label in DailyMed indicates that pregabalin leads to epididymitis, which can negatively impact sperm production, a study published in early 2015 concluded that pregabalin did not negatively impact sperm production in healthy volunteers [ 14 ]. It is therefore unclear whether the percentage of affected patients (reported to be ∼1% in the drug label) was too low to lead to a significant finding in the recent clinical trial, or whether the epididymitis in these patients was not associated with decreased spermatogenesis.…”
Section: Limitations Of This Review and Future Directionsmentioning
confidence: 99%
“…Not all of the studies included in our review used the most up to date edition of the WHO criteria available when conducting their trial. Studies defining semen analysis parameters using WHO 1992 criteria were commenced in 2012 and 2006 and could have utilized the WHO 1999 criteria when conducting the trial ( Selice et al , 2011 ; Sikka et al , 2015 ). A similar issue was identified with some studies defining semen analysis criteria using WHO 1999 , where the trial was commenced in 2013 or 2016 after the introduction of WHO 2010 ( Haje and Naoom, 2015 ; Hosseini et al , 2016 ; Tehrani et al , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sikka et al. (2015) concluded that PG did not negatively impact sperm production in healthy volunteers. They reported that a percentage of >50% decrease in sperm count in PG receivers (9.2%) than placebo (3.2%), but the 95% CI was not inferior to placebo statistically and sperm motility decreased by PG administration but did not reach a significant level.…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin (PG) was associated with reversible effects on sperm parameters (decreased sperm count and motility, and increased sperm abnormalities) and reproductive function (reduced fertility and increased embryo loss) and birth defects in the pre‐clinical animal studies (Ding et al., 2017; Etemad, Mohammad, Mohammadpour, Mashhadi, & Moallem, 2013). However, in clinical trials, treatment with 600 mg/day PG for 12 weeks did not significantly affect spermatogenesis or serum levels of FSH and testosterone in healthy males volunteers (Sikka et al., 2015).…”
Section: Introductionmentioning
confidence: 99%